Womens Perceptions of their Career Prospects: A Case Study of Hong Kong based Japanese Companies - Lam, On Tin (2006)
This study examined women employees perceptions toward their career prospects in Hong Kong based Japanese companies (HKJC). 20 women employees from different sizes and industries of HKJC were interviewed. This article mainly focuses on how women think about their current and future career prospects in HKJC. Through examining the description of career from women employees, several problems such as discrimination, the presence of Glass ceiling, the Japanese management systems and its traditional culture and perception, which affected womens motivation and job satisfaction a lot, to a great extent were identified and illuminated. Further women employees reaction to the problems will be discussed. There are some improvements in Japanese perception toward women, but the study confirms that women still lacked chance in having career advancement. The study affirms that the women career development in HKJC is not very developed not only because of traditional perception to women, but also the Japanese culture to outsiders (nationality difference).